Evaluating the effects of seed oils on lipid profile, inflammatory and oxidative markers, and glycemic control of diabetic and dyslipidemic patients: a systematic review of clinical studies - Fornari Laurindo, Lucas; Fornari Laurindo, Lívia; Dogani Rodrigues, Victória; da Silva Camarinha Oliveira, Jéssica; Leme Boaro, Beatriz; Cressoni Araújo, Adriano; Landgraf Guiguer, Elen; Rucco Penteado Detregiachi, Claudia; Maria Cavallari Strozze Catharin, Virgínia; Federighi Baisi Chagas, Eduardo; Cavallari Strozze Catharin, Vitor; Direito, Rosa; et al. (Frontiers in Nutrition, 2025)
Diabetes mellitus and dyslipidemia are significant health concerns that elevate the risk of cardiovascular disease and other metabolic disorders, necessitating effective management strategies. Recent research has highlighted the potential role of dietary fats, particularly seed oils, in influencing health outcomes in these conditions. This systematic review evaluates the impact of seed oils on lipid profiles, inflammatory and oxidative markers, and glycemic control in patients with diabetes and dyslipidemia. A comprehensive search across databases, including PubMed, Scopus, Web of Science, Cochrane Library, and Google Scholar, identified studies focusing on the effects of seed oils. The studies include randomized controlled, parallel-design, double-blind, placebo-controlled, and open-label studies published in English. The quality of the studies was assessed through a detailed review process, and data were extracted to evaluate the effects of seed oils on key metabolic markers. The review included 11 studies demonstrating that seed oils derived from canola, flaxseed, and sesame seeds can positively influence lipid profiles and glycemic control while potentially modulating oxidative stress markers. The findings suggest that seed oils may benefit in managing diabetes and dyslipidemia, although the results are sometimes inconsistent. This review provides valuable insights for dietary recommendations and therapeutic strategies, highlighting the need for further research to clarify the role of seed oils in metabolic health.